Linearization of a Matrix Riccati Equation Associated to an Optimal Control Problem. (6th April 2014) - Zitouni, Foued; Lefebvre, Mario
Abstract : The matrix Riccati equation that must be solved to obtain the solution to stochastic optimal control problems known as LQG homing is linearized for a class of processes. The results generalize a theorem proved by Whittle and the one-dimensional case already considered by the authors. A particular two-dimensional problem is solved explicitly.